2017
DOI: 10.1016/j.jdsr.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptides and ATP signaling in the trigeminal ganglion

Abstract: SummaryPeripheral nociceptive stimuli from orofacial structures are largely transmitted by the trigeminal nerve. According to the peripheral noxious stimuli, neurons in the trigeminal ganglion (TG) produce neuropeptides such as substance P, and calcitonin-gene-related peptide, etc. Beside the production of neuropeptides, there exists unique non-synaptic interaction system between maxillary and mandibular neurons in the TG. Neurons in the TG are surrounded by satellite glial cells (SGCs), which initially receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 84 publications
(86 reference statements)
2
52
0
Order By: Relevance
“…The activity of spinal trigeminal neurons with afferent input from inflamed temporomandibular joint and facial skin was decreased by injection of an NK1 receptor antagonist into the trigeminal ganglion (Takeda et al 2012). However, it is not likely that NK1 receptors in the trigeminal ganglion are crucially involved in the generation of migraine pain, since NK1 receptor antagonists are ineffective in migraine therapy or prevention of migraine (Goldstein et al 1997(Goldstein et al , 2001. PACAP binds to the three receptor subtypes of the VIP/PACAP receptor family, VPAC1, VPAC2 and PAC1, immunoreactivity of which was found in small diameter neurons in rat and human trigeminal ganglion (Chaudhary and Baumann 2002;Knutsson and Edvinsson 2002).…”
Section: Neuropeptide Receptors In the Trigeminal Ganglionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of spinal trigeminal neurons with afferent input from inflamed temporomandibular joint and facial skin was decreased by injection of an NK1 receptor antagonist into the trigeminal ganglion (Takeda et al 2012). However, it is not likely that NK1 receptors in the trigeminal ganglion are crucially involved in the generation of migraine pain, since NK1 receptor antagonists are ineffective in migraine therapy or prevention of migraine (Goldstein et al 1997(Goldstein et al , 2001. PACAP binds to the three receptor subtypes of the VIP/PACAP receptor family, VPAC1, VPAC2 and PAC1, immunoreactivity of which was found in small diameter neurons in rat and human trigeminal ganglion (Chaudhary and Baumann 2002;Knutsson and Edvinsson 2002).…”
Section: Neuropeptide Receptors In the Trigeminal Ganglionmentioning
confidence: 99%
“…Many of the gene products like CGRP, CGRP receptor proteins and BDNF can crucially influence neuronal transduction and synaptic transmission, because they are delivered by axonal transport through the neuronal processes to the peripheral and/or central terminals of trigeminal afferents Other signaling mechanisms between primary afferent neurons, SGCs and immune cells do not directly involve neuropeptides and NO. Intraganglionic signaling by ATP has been reviewed elsewhere (Goto et al 2017). Neurons may signal via ATP to other neurons and to SGCs, and these may signal to microglia/macrophage-like cells (MLCs).…”
Section: Intercellular Cross-talk Within the Trigeminal Ganglionmentioning
confidence: 99%
“…The neurotransmitters glutamate and ATP have also been implicated in the communication within the trigeminal ganglion. Experimental studies have demonstrated the expression of excitatory glutamate receptors and ATP receptors in sensory neurons [140,141].…”
Section: Intraganglionic Mechanisms Involved In Nociceptor Sensitizationmentioning
confidence: 99%
“…For a long time after the IANX, various molecules are generated in uninjured, as well as injured, trigeminal ganglion (TG) neurons, which are sensitized [5]. Neuropeptides, ATP, and chemokines are produced in TG neurons, and these molecules are released from TG neurons with injured axons [6]. Takeda et al reported that after temporomandibular joint inflammation, substance P (SP) production is enhanced in small-diameter TG neurons, which release SP via a paracrine mechanism [7].…”
Section: Introductionmentioning
confidence: 99%
“…Many of the GFAP-IR cells in the TG also express the P2Y 12 receptor, suggesting that ATP is released from TG neurons and binds to the P2Y 12 receptor to activate satellite glial cells. SP, calcitonin gene-related peptide (CGRP), and tumor necrosis factor α are also released from TG neurons and involved in the activation of satellite glial cells [6]. Furthermore, connexin 43 expression is significantly enhanced in satellite glial cells suggesting that propagation of satellite glial cell activation occurs via connexin 43 [12].…”
Section: Introductionmentioning
confidence: 99%